Investigation Some Adhesions Genes of P. Mirabilis and E. Coli Isolated from Urinary Tract Infections - Jaber, Hassanain Hataf (Journal of Science in Medicine and Life, 2025)
This research was carried out to determine the prevalence and virulence traits of Escherichia coli and Proteus mirabilis in UTI patients. Bacterial isolates were characterized by routine cultural, microscopic, and biochemical examinations as well as VITEK2 compact system. The most frequently isolated organism was E. coli (n=28, 35%), followed by P. mirabilis (n=14, 17%). Hemagglutination assays with human blood group O+ erythrocytes were performed to evaluate virulence phenotypes. P. mirabilis strains has 50% (MRHA), 42.86%(MSHA) and only (NOHA) of the isolates could have mannose Resistant hemagglutination activity respectively. The percentages of the E. coli isolates were as follows: MSHA 30%, MRHA 26.67% (3), and NOHA 43.33%. In addition, adhesion assays demonstrated high affinities to uroepithelial cells with E. coli 20–110 bacteria/cell and P. mirabilis 30–60 bacteria/cell. Expression of adhesin-encoding genes afaB and fimH for both species was subsequently verified by molecular analysis. Statistical analysis indicated significant differences among the expression of virulence genes of these Ur pathogens. The fact that both fimbrial and afimbrial adhesins play a role in UTI pathogenesis suggests FimH and AfaB as candidate targets for an anti-adhesion treatment.